Develop and Engage Talents: A Preliminary Study at Islamic Banks in Northern Region of Malaysia - Bidayatul Akmal Mustafa Kamil; Fatin Izzati Iqbal (Journal of Accounting and Finance in Emerging Economies, 2017)
Purpose: Attract, select, develop and engage the right talents at the right time, place and position become essential for upgrading the management system in the banking sector. This study identifies the development of talents through talent management and succession planning, which may engage those employees with the banks.